Ionic selectivity of the sodium channel of frog skeletal muscle (The Rockefeller University Press, 1976)
The ionic selectivity of the Na channel to a variety of metal and organic cations is studied in frog semitendinosus muscle. Na channel currents are measured under voltage clamp conditions in fibers bathed in solutions with all Na+ replaced by a test ion. Permeability ratios are calculated from measured reversal potentials using the Goldman- Hodgkin-Katz equation. The permeability sequence was Na+ approximately Li+ approximately hydroxylammonium greater than hydrazinium greater than ammonium greater than guanidinium greater than K+ greater than aminoguanidinium in the ratios 1:0.96:0.94:0.31:0.11:0.093:0.048:0.031. No inward currents were observed for Ca++, methylammonium, methylguanidinium, tetraethylammonium, and tetramethylammonium. The results are consistent with the Hille model of the Na channel selectivity filter of the node of Ranvier and suggest that the selectivity filter of the two channels is the same.